2022
DOI: 10.1088/2515-7655/aca4a2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of hexamethylguanidinium bis(fluorosulfonyl)imide [HMG][FSI] based electrolyte and its application in sodium metal batteries

Abstract: With the increasing energy demand for both electronic portable devices and energy storage for fluctuating renewable energy sources, there is a strong need for alternatives beyond lithium batteries. Sodium batteries have been attracting great attention recently due to the abundance and low supply cost of the raw materials. However, they require highly conductive, safe and electrochemically stable electrolytes in order to enable their practical realization. In this work we present the promising physicochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…53,54 It is also a reasonable assumption for liquid electrolytes taken from literature. 55,56 It can be shown that writing Eq. 4 for the two species and holding the electroneutrality condition reduces Eq.…”
Section: Na Tmentioning
confidence: 99%
“…53,54 It is also a reasonable assumption for liquid electrolytes taken from literature. 55,56 It can be shown that writing Eq. 4 for the two species and holding the electroneutrality condition reduces Eq.…”
Section: Na Tmentioning
confidence: 99%
“…85,215 Compared with BLTE, ES6-BLTE has a lower desolvation energy (À157.5 kcal mol À1 ), indicating that Na + in ES6-BLTE electrolyte has a low desolvation barrier and accelerated interfacial transfer dynamics. 85,215 Notably, the desolvation energy of Na + is an important indicator for evaluating batteries, especially in LT environments. 115,130,179 Fig.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…The high mechanical strength hinders the penetration of Na dendrites dramatically, thereby minimizing safety hazards. 167,179,215 Fig. 6e shows a Na|Na symmetric cell with the ES6-BLTE electrolyte tested at 0.1 mA cm À2 and 0.1 mA h cm À2 .…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…For example, the hexamethylguanidinium FSI, [HMG][FSI], OIPC was recently used as an electrolyte and presented interesting properties when mixed with Na and Li salts. [39][40][41][42] Biernacka et al investigated the effect of different anions and salt concentrations on the physicochemical properties of [HMG][FSI] by creating mixtures of [HMG][FSI]/LiFSI and [HMG][FSI]/LiTFSI. The results showed that 50 mol% LiFSI or LiTFSI in [HMG][FSI] is liquid with glass transition temperatures at À58 1C and À50 1C, respectively, whereas, [HMG][FSI] with 10 mol% and 90 mol% of LiFSI or LiTFSI acts as quasi-solid electrolytes with melting points at 89 1C for 90 mol% LiFSI and 120 1C for 90 mol% LiTFSI.…”
Section: Introductionmentioning
confidence: 99%